Design and optimisation of a high performance lightweight monoblock cast iron brake disc - Topouris, Stergios (Cranfield University, 2017)
In the past few decades, part weight reduction that would yield lower fuel consumption and decrease CO₂ emissions has been one of the main challenges in the automotive industry. In brake rotors, the downsizing is even more difficult because mass reductions may result in lower thermal capacity which will compromise rotors performance. This research work focuses on developing a design methodology for a novel concept of a lightweight monoblock brake disc with fingered hub. Discs of such a design can feature reduced mass, lower cost, improved cooling and are particularly suitable for Electric and Hybrid Electric Vehicles. The described methodology comprises a number of steps, each investigating a different attribute of this novel disc design and ensuring its feasibility. The use of Finite Element Analysis was incorporated to study the mechanical and thermomechanical loading on the disc with the results indicating acceptable behaviour. Physical testing with an actual prototype disc confirmed the findings of the modelling work. Thereafter, structural optimisation was conducted where significant reduction in mechanical stress was achieved and also further weight reductions. Finally, in a newly developed experimental facility cooling tests were conducted that revealed substantially improved cooling characteristics for the brake disc with fingered hub when compared to the baseline solid hub disc.
Keywords: Finite Element Analysis; Structural Optimisation; Lightweight Brake Disc; Fingered Hub; Brake Disc Cooling; Disc Cooling Rig